Predictor of Business Students’ Attitudes Toward Sustainable Business Practices - Ng, Eddy S. (Journal of business ethics, 2010)
This study examined individual difference characteristics as predictors of business students’ attitudes toward sustainable business practices. Three types of predictors were considered: personal values, individualism–collectivism, and leadership styles. Data were collected from 248 business students attending a mid-sized university in western United States using self-reported questionnaires. Few gender differences were present. Hierarchical regression analyses, controlling for personal demographic characteristics, indicated that business students scoring higher on Rokeach’s social value scale, collectivism, and transformational leadership also reported more positive attitudes toward sustainable business practices. Implications for research and practice are discussed.